Dinamika Hubungan Gereja dan Negara: Studi Kasus Pemikiran Tokoh Reformasi terhadap Otoritas Sipil - Nadia Blessy Pelealu (Views : Jurnal Teologi dan Biblika, 2026)
This study examines the dynamic relationship between church and state through the ideas of Reformers such as Matin Luther, John Calvin, and Huldrych Zwingli, as they relate to their understanding of public authority. This study employs are analyzed descriptively, historically, and comparatively. The findings reveal that each of the three Reformers adopted a distinct approach. Luther emphasized the doctrineof the two kingdoms, distinguishing beetwen spiritual and secular authority, both of which are subyek to God’s sovereignty. Calvin described the complementary duality of governmental functions between church and state without dimishing the authority of either. Zwingli, on the other hand, developed an integrative approach that unites the roles of church and state in shaping the social order. These differences demonstrate that there is no single model for the relationship between church and state, but rather various approaches influenced by social, political, and theological contexts. Therefore, the ideas of the Reformers have made a significant contribution to the further development of understanding regarding the relationship between church and state in the modern context.